Green School - Serra, S.; Afonso, P.; Duarte, T. (Open Schools Journal for Open Science, 2020)
The interdisciplinary project, including the school disciplines of Natural Sciences, Mathematics, Expressions, Portuguese, ICT, History, and geography of Portugal. The project emerged from the students’ interests and needs when observing the school space. An action plan for the improvement of green spaces was created through the creation of a school garden. The students were involved in planning, creating partnerships, executing and maintaining the project. During the school year, there was a change in behaviour in relation to the garden and the care for the school green spaces by the students involved, but also by the school community.